Gender disparity In arabic education in the 21st century in Nigeria: problems and solutions (2012)
Any education which does not immediately benefit a person either in finding employment or to improve his/her living conditions, would not attract public attention. Therefore, Arabic education in Nigeria particularly for women should be designed so as to lead to useful work life. Arabic, being a Semitic language of major religion and culture which demands some skills and lengthy duration before its learners could attain an appreciable level for useful work life in Nigeria .This prerequisite has made the Language suffered a lot of setback from women fold due to some of the impediments of its learning by females which were traceable to religious, cultural bonds, time factor and economic crisis. The paper aims at examining the gender inequity in Arabic education in the 21st century in Nigeria. Such impediments, the erroneous impression and perception of the society, parents, learners and the teachers on the language were critically examined. It will explore options that could provide women better avenues for Arabic education. It also advocates for equal opportunities of gender in access to education for women, the use of relevant modem materials and techniques for the teaching and learning of Arabic in Nigeria to meet current challenges.